ENHANCING MOTHER’S KNOWLEDGE OF COMMUNITY-LED TOTAL SANITATION PRACTICES THROUGH HEALTH EDUCATION INTERVENTIONS IN JUMPUTREJO VILLAGE, SIDOARJO - Drastyana, Serlly Frida; Prasetyorini, Anif; Ali, Amir; Sutha, Diah (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2025)
Introduction: The report shows a decrease in stunting prevalence at the national level by 6.4% over 5 years.  The problem of stunting in the future directly affects prospective mothers. The aim of health education is to increase the knowledge of mothers of stunted infants and toddlers about environmental factors as the cause of stunting. Methods: The method of implementation in the health education program is through providing knowledge on stunting to mothers of stunted babies and toddlers in the Jumputrejo Village. The participants are mothers of infants and toddlers in Jumputrejo Village, totaling 18 people. The method for education to increase the knowledge of mothers of stunted infants and toddlers about personal hygiene, mothers of stunted infants and toddlers about environmental sanitation, and increase the knowledge of mothers of stunted infants and toddlers about environmental factors that cause stunting. Variables of this community services are knowledge before and after giving health education. Instrument of this study using questionnaire and data analysis using t test. Results: The knowledge increase before and after giving assistance, counseling, and health education about community-based total sanitation. The results of community service found that there was a difference between the knowledge pretest and post-test with a significance of 0.000. Conclusion: Knowledge about community-based total sanitation increased because they received proper education, awareness campaigns, and hands-on training on sanitation practices. Mothers of young children received health education, and afterward, community-led sanitation was covered through a question-and-answer format. Further evaluation can be done to measure the extent to which the increase in knowledge brings changes in the sanitation behavior of the local community and the prevention of stunting.